A Case of Fatal Gastrointestinal Anthrax in North Eastern Iran. (31st March 2015) - Hashemi, Seyed Ahmad; Azimian, Amir; Nojumi, Sara; Garivani, Tahereh; Safamanesh, Saghar; Ghafouri, Majid
Abstract : Background. Bacillus species are aerobic or facultative anaerobic, gram-positive, or gram-variable spore-forming rods. They are ubiquitous in the environmental sources. Bacillus anthracis may usually cause three forms of anthrax: inhalation, gastrointestinal, and cutaneous. The gastrointestinal (GI) anthrax develops after eating contaminated meat. In this paper we report septic intestinal anthrax. Case Presentation . We report an isolation of Bacillus anthracis from blood culture of patient with intestinal anthrax. Bacillus anthracis was isolated from a blood culture of a 34-year-old man who had a history of severe abdominal pain, bloody diarrhea, nausea, vomiting, fever, sweating, and lethargy within 4 to 5 days after eating the meat of domestic goat. He had evidence of severe infection and septic shock and did not respond to treatments and subsequently expired 9 hours after hospitalization. Conclusion . Gastrointestinal anthrax is characterized by rapid onset, fever, and septicemia. Rapid diagnosis and prompt initiation of antibiotic therapy can help in survival. Most of previous cases of septicemic anthrax were related to injection drug users but, in our case, septicemia occurred after gastrointestinal anthrax.